The Regulation of Pea (Pisum sativum L.) Symbiotic Nodule Infection and Defense Responses by Glutathione, Homoglutathione, and Their Ratio - Ivanova, Kira A.; Chernova, Ekaterina N.; Kulaeva, Olga A.; Tsyganova, Anna V.; Kusakin, Pyotr G.; Russkikh, Iana V.; Tikhonovich, Igor A.; Tsyganov, Viktor E. (Frontiers in Plant Science, 2022)
In this study, the roles of glutathione (GSH), homoglutathione (hGSH), and their ratio in symbiotic nodule development and functioning, as well as in defense responses accompanying ineffective nodulation in pea (Pisum sativum) were investigated. The expression of genes involved in (h)GSH biosynthesis, thiol content, and localization of the reduced form of GSH were analyzed in nodules of wild-type pea plants and mutants sym33-3 (weak allele, ‘locked’ infection threads, occasional bacterial release, defense reactions) and sym33-2 (strong allele, ‘locked’ infection threads, defense reactions), and sym40-1 (abnormal bacteroids, oxidative stress, early senescence, defense reactions). The effects of (h)GSH depletion and GSH treatment on nodule number and development were also examined. The GSH: hGSH ratio was found to be higher in nodules than in uninoculated roots in all genotypes analyzed, with the highest value being detected in wild-type nodules. Moreover, it was demonstrated, that a hGSHS-to-GSHS switch in gene expression in nodule tissue occurs only after bacterial release and leads to an increase in the GSH: hGSH ratio. Ineffective nodules showed variable GSH: hGSH ratios that correlated with the stage of nodule development. Changes in the levels of both thiols led to the activation of defense responses in nodules. The application of a (h)GSH biosynthesis inhibitor disrupted the nitrogen fixation zone in wild-type nodules, affected symbiosome formation in sym40-1 mutant nodules, and meristem functioning and infection thread growth in sym33-3 mutant nodules. An increase in the levels of both thiols following GSH treatment promoted both infection and extension of defense responses in sym33-3 nodules, whereas a similar increase in sym40-1 nodules led to the formation of infected cells resembling wild-type nitrogen-fixing cells and the disappearance of an early senescence zone in the base of the nodule. Meanwhile, an increase in hGSH levels in sym40-1 nodules resulting from GSH treatment manifested as a restriction of infection similar to that seen in untreated sym33-3 nodules. These findings indicated that a certain level of thiols is required for proper symbiotic nitrogen fixation and that changes in thiol content or the GSH: hGSH ratio are associated with different abnormalities and defense responses.